Psychosocial factors and caregiver burden among primary family caregivers of frail older adults with multimorbidity - Chan, Cheuk Ying (2023)
Background: Provision of care for frail older adults with multiple chronic diseases (multimorbidity) poses increasing challenge for family caregivers. Our study aims to evaluate to what extent caregiving competence, social support and positive aspects of caregiving can mitigate the effect of burden experienced by family caregivers of frail older adults with multimorbidity. Methods: A descriptive cross-sectional study was conducted in 2 primary care clinics. Family caregivers of older adults aged 65 years and above were invited to complete interviewer-administered questionnaires. Descriptive statistics were used to describe sociodemographic and clinical data. Caregiver’s burden was measured using the Zarit Burden Interview (ZBI). Mann–Whitney U test was used to compare differences in Caregiving Competence Scale (CCS), short Positive Aspects of Caregiving (S-PAC) and modified Medical Outcome Study Social support (mMOS-SS). Multivariable logistic regression was used to analyse factors associating with caregiver burden. Results: A total of 188 participants were recruited. 71.8% reported caregiver burden (ZBI score ≥ 10). Caregivers who perceived burden had significantly lower CCS, S-PAC and mMOS-SS scores than those who did not (10.0 vs 11.6; 26.8 vs 29.8; 24.8 vs 31.4, p < 0.001 respectively). Factors significantly associated with higher odds of perceived burden were presence of alternative caregivers (OR 3.3, 95% CI 1.09, 10.19, p = 0.04), use of community resources (OR 4.4, 95% CI 1.15, 16.83, p = 0.03) and time spent caregiving per week (OR 1.1, 95% CI 1.02, 1.10, p = 0.003). Discussion and conclusion: This study found that caregivers had high perception of burden as demand in caregiving may increase. Anticipating caregiver burden and social support needs may be important part of managing these frail older adults.